Agresión sexual y su influencia en las relaciones sociales en una adolescente de 13 años - Vera Jimenez, Misael Nathael (2020)
Sexual assault is a social problem in which people are immersed regardless of the type of sex, age, race or economic condition. However, we must know how to differentiate between the different types of coercion to which the victims are being subjected, since sexual assault is considered as a deliberate act opting for the use of force to maintain intimacy. This paper deals with a case study about sexual assault which aims to determine if this act influences the social relationships of the individual. It addresses the consequences of this type of violence and, in turn, the reasons why the victim does not express his situation. To obtain information, different techniques and tools are proposed during the course of the study, which are consistent with the fulfillment of the objective set by the researcher. In the same way, a diagnosis of the unit of analysis is reached to later elaborate a therapeutic plan that will be proposed for the evolution of the victim and thus improve their living condition.